THE DISCOURCE OF DRESS CODE IN ISLAMIC LAW - Rusjdi Ali Muhammad; Dedy Sumardi (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2019)
The discussion concerning dress code or clothing will always be closely related to the debate of aurat or ‘awrah, as the clothing mainly serves to cover aurat. The ‘awrah (in Arabic) or aurat (in Bahasa) is the parts of the body which must be covered with clothing. The boundary of the aurat in the Islamic jurisprudence (fiqh) study is associated with the prayer (salah), which is then ascribed to the boundary of the aurat beyond prayer, based on qiyas. The thinking framework of fuqaha’ (the expert in Islamic law) in their attempt to cover the aurat of Muslim men and women refers to common terms, such as hijab, jilbab, khimar, dir sabigh and milhaf. Even though these terms do not represent the standard form and model of dressing, they are adequate to reveal the restriction of dressing based on Islamic teaching (shariah). The absence of a standard formulation for the form and model of Islamic dressing indicates that Islamic teachings are flexible for the discovery of ideal forms and models of clothing adhering to religious norms, ethics and moral teachings. Clothing is part of the cultural product as well as religious and moral requirements without denying the custom of society. Abstrak: Pembahasan tentang busana/pakaian akan senantiasa terkait erat dengan pembahasan aurat, karena fungsi utama pakaian adalah sebagai penutup aurat. Batasan aurat dalam kajian fiqh Islam dikaitkan dengan ibadah shalat, yang kemudian diaplikasikan kepada batasan aurat di luar shalat, berdasarkan qiyas. Landasan berpikir yang digunakan fuqaha' dalam upaya menutup aurat laki-laki dan perempuan muslim merujuk pada istilah umum seperti hijab, jilbab, khimar, dir sabigh dan milhaf. Meskipun istilah-istilah ini belum mewakili bentuk dan model busana/pakaian yang baku, tetapi mampu mengungkap batasan makna busana/pakaian dalam ajaran Islam. Tidak adanya rumusan baku tentang bagaimana bentuk dan model busana/pakaian islami mengindikasikan bahwa ajaran Islam memberi keleluasaan dalam menemukan bentuk dan model pakaian ideal yang tetap mengacu pada norma-norma agama, etika dan ajaran moral. Pakaian merupakan bagian dari produk budaya sekaligus tuntunan agama dan moral tanpa menafikan adat kebiasaan suatu masyarakat. Kata Kunci: Pakaian, Aurat, Fiqh